From theory to experiment: BaFe0.125Co0.125Zr0.75O3−δ, a highly promising cathode for intermediate temperature SOFCs. Issue 6 (28th January 2020) - Sánchez-Ahijón, Elena; Marín-Gamero, Rafael; Molero-Sánchez, Beatriz; Ávila-Brande, David; Manjón-Sanz, Alicia; Fernández-Díaz, M. Teresa; Morán, Emilio; Schmidt, Rainer; Prado-Gonjal, Jesús
Abstract : BaFe0.125 Co0.125 Zr0.75 O3− δ perovskite is a novel and efficient MIEC electrode for IT-SOFCs. Symmetrical cells with an area-specific resistance of 0.13 Ω cm 2 at 700 °C and 0.05 Ω cm 2 at 800 °C have been prepared. Abstract : In a recent theoretical study [Jacobs et al., Adv. Energy Mater., 2018, 8, 1702708], BaFe0.125 Co0.125 Zr0.75 O3− δ was predicted to be a stable phase with outstanding performance as an auspicious cathode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). It is shown here that the theoretical predictions are valid. The material can be synthesized by the citrate method as a single cubic Pm 3̄ m phase with a significant amount of oxygen vacancies, randomly distributed in the anionic sublattice facilitating oxygen vacancy conduction. A thermal expansion coefficient of 8.1 × 10 −6 K −1 suggests acceptable compatibility with common electrolytes. Electrochemical impedance spectroscopy of symmetrical cells gives an area-specific resistance of 0.33 Ω cm 2 at 700 °C and 0.13 Ω cm 2 at 800 °C. These values are reduced to 0.13 Ω cm 2 at 700 °C and 0.05 Ω cm 2 at 800 °C when the material is mixed with 30 wt% Ce0.9 Gd0.1 O2− δ .